Photochemistry of Nitrated Polycyclic Aromatic Hydrocarbons under Solar Radiation - Ostojic, Bojana D.; Dordevic, Dragana S. (Current Organic Chemistry, 2018)
This manuscript gives a summary of photoinduced processes in several Nitropolycyclic Aromatic Hydrocarbons (NPAHs) (nitronaphthalene, nitrofluorene, nitroanthracene, and nitropyrene) as well as the results of the TD-DFT calculations of the excited states and the geometries in the ground and first singlet excited electronic states of three isomers of nitrophenanthrene (1NPh, 3NPh, and 9NPh) which are presented for the first time. The decay of the first excited singlet state can lead to different pathways depending on a variety of factors: the energy gap between the S1 state and the nearest state from the triplet manifold, geometries of the electronic states, electronic configuration of the states, etc. The gas phase NPAH molecule can bind to particulate matter in the atmosphere and different solvents present in the aerosol can activate or inhibit photoprocesses. These events depend strongly on the solvent polarity. We reviewed experimental studies that explored these variations of photoinduced processes in conjuction with TD-DFT and ab initio computations.
Keywords: time-resolved photoelectron spectroscopy